Realized moments and bond pricing - Barbora Malinska (Charles University in Prague, Institute of Economic Studies (IES), 2019)
This paper examines both intertemporal and contemporaneous relationship between excess US Treasury futures returns and realized moments - realized volatility, realized skewness and realized kurtosis using high-frequency data. We find realized skewness to have significant negative effect on future excess returns, on the contrary realized volatility and realized kurtosis remain insignificant. Moreover, in addition to strong explanatory power of realized skewness for contemporaneous excess returns, we find evidence of intra-temporal returnvolatility trade-off dependent on skewness regime (i.e. positive or negative skewness).
Keywords: C32; C55; G12; 330; Realized moments; bond pricing; risk-return trade-off; high-frequency data